Differences between men and women in dietary intakes and metabolic profile in response to a 12-week nutritional intervention promoting the Mediterranean diet. (13th April 2015) - Leblanc, Vicky; Hudon, Anne-Marie; Royer, Marie-Michelle; Corneau, Louise; Dodin, Sylvie; Bégin, Catherine; Lemieux, Simone
Abstract Few studies have compared men and women in response to nutritional interventions but none has assessed differences between men and women in the response to a nutritional intervention programme based on the self-determination theory (SDT) and using the Mediterranean diet (MedDiet) as a model of healthy eating, in a context of CVD prevention and within a non-Mediterranean population. The present study aimed to document differences between men and women in changes in dietary, anthropometric and metabolic variables, in response to a nutritional intervention programme promoting the adoption of the MedDiet and based on the SDT. A total of sixty-four men and fifty-nine premenopausal women presenting risk factors for CVD were recruited through different media advertisements in the Québec City Metropolitan area (Canada). The 12-week nutritional programme used a motivational interviewing approach and included individual and group sessions. A validated FFQ was administered to evaluate dietary intakes from which a Mediterranean score (Medscore) was derived. Both men and women significantly increased their Medscore in response to the intervention (P < 0·0001). Men showed a significantly greater decrease in red and processed meat (−0·4 (95 % CI −0·7, −0·1) portions per d) and a greater increase in fruit (0·9 (95 % CI 0·2, 1·6) portions per d) intakes than women. Significant decreases were observed for BMI and waist circumference in both men and women (P ≤ 0·04). Significant greater decreases were found for total cholesterol (total-C):HDL-cholesterol (HDL-C) (−0·2; 95 % CI −0·4, −0·03) and TAG:HDL-C (−0·2; 95 % CI −0·4, −0·04) ratios in men than in women. When adjusting for the baseline value of the response variable, differences between men and women became non-significant for red and processed meat and fruit intakes whereas significant differences between men and women (i.e. larger increases in men than women) were observed for legumes, nuts and seeds (0·6 (95 % CI 0·2, 1·0) portions per d) and whole-grain products (0·5 (95 % CI 0·01, 1·0) portions per d) intakes. For metabolic variables, differences between men and women became non-significant for total-C:HDL-C and TAG:HDL-C ratios when adjusted for the baseline value of the response variable. The present results suggest that the nutritional intervention promoting the adoption of the Mediterranean diet and based on the SDT led to greater improvements in dietary intakes in men than in women, which appear to have contributed to beneficial anthropometric and metabolic changes, more particularly in men. However, the more deteriorated metabolic profile found in men at baseline seems to contribute to a large extent to the more beneficial changes in CVD risk factors observed in men as compared with women.